A mobile application for assessing the product success on crowdfunding campaign: the development and usability testing - Yanti Pasmawati; Titis Wijayanto; Alva Edy Tontowi; Budi Hartono (Jurnal Sistem dan Manajemen Industri, 2021)
Crowdfunding is one of the alternative sources of finance for product-based startups. Products are funded if the campaign is considered to be successful in reaching the target. The assessment of the success rate of product campaigns develops into three successive levels, namely overfunding, successful and unsuccessful. Due to the complication of setting up a product campaign on an online crowdfunding platform, a mobile application to aid campaigners needs to be developed. Moreover, it is essential to evaluate its ease to use. This study aims to (1) develop an android-based application, (2) evaluate the usability of the application based on user perceptions. The application ('POSCA') was developed by emphasizing user experience (UX), while the Use Questionnaire evaluated its usability. Ten participants were invited to evaluate the system usability and interface. The results suggest that 'POSCA' has good scores of usability: ‘efficiency’ = 49.11% in the fifth trial, ‘very-easy-to-learn’ (95%), ‘useful’ (85%), ‘easy-to-use’ (87%), and ‘satisfy-the-users’ (88%).